Comparison of existing 3D food printers - Toh, Wei Yan (2018)
3D food printing is a new area of research and development, where there have been several-kinds of 3D food printers developed and used. However, most of these 3D printers are yet mature to be able to overcome the restrictions encountered. Therefore, this paper provides a review on existing 3D food printers by comparing their advantages, limitations as well as future looks up.